2014
DOI: 10.1016/j.chemosphere.2014.09.087
|View full text |Cite
|
Sign up to set email alerts
|

Uranium(VI) reduction by nanoscale zero-valent iron in anoxic batch systems: The role of Fe(II) and Fe(III)

Abstract: The role of Fe(II) and Fe(III) in U(VI) reduction by nanoscale zerovalent iron (nanoFe0) was investigated using two iron chelators 1,10-phenanthroline and triethanolamine (TEA) under a CO2-free anoxic condition. The results showed that U(VI) reduction was strongly inhibited by 1,10-phenanthroline and TEA in a pH range from 6.9 to 9.0. For instance, at pH 6.9 the observed U(VI) reduction rates decreased by 81% and 82% in the presence of 1,10-phenanthroline and TEA, respectively. The inhibition was attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…This literature confirmed that U 6+ was predominantly removed by nZVI via reductive precipitation of UO 2 2+ (U 4+ ) with minor precipitation of UO 3 •2H 2 O (U 6+ ) as confirmed by the Xray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) analyses. Oxygen level, solution pH, and presences of bicarbonates and calcium ions all affect the reductive immobilization processes [84,85]. It has also been reported that nZVI was able to reduce higher valent Cr +6 to low valent Cr +3 in water or soil media.…”
Section: Nanoscale Zero-valent Iron Particles (Nzvi)mentioning
confidence: 98%
See 1 more Smart Citation
“…This literature confirmed that U 6+ was predominantly removed by nZVI via reductive precipitation of UO 2 2+ (U 4+ ) with minor precipitation of UO 3 •2H 2 O (U 6+ ) as confirmed by the Xray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) analyses. Oxygen level, solution pH, and presences of bicarbonates and calcium ions all affect the reductive immobilization processes [84,85]. It has also been reported that nZVI was able to reduce higher valent Cr +6 to low valent Cr +3 in water or soil media.…”
Section: Nanoscale Zero-valent Iron Particles (Nzvi)mentioning
confidence: 98%
“…These risks can be remediated by reducing it to insoluble U 4+ oxides by nZVI. Several related reports have shown that, compared to the other reductants such as metal iron filing, galena (PbS), and iron sulfide, nZVI is very efficient to reductively immobilize U 6+ from aqueous phase, which could be attributed to its nanosize, high reactivity, large surface area, and reactive Fe(II) produced by nZVI [84][85][86][87][88]. This literature confirmed that U 6+ was predominantly removed by nZVI via reductive precipitation of UO 2 2+ (U 4+ ) with minor precipitation of UO 3 •2H 2 O (U 6+ ) as confirmed by the Xray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) analyses.…”
Section: Nanoscale Zero-valent Iron Particles (Nzvi)mentioning
confidence: 99%
“…Based on these reactions, corrosion of the nZVI not only affects the surface and chemical properties of nZVI, but also impacts the aqueous chemistry, such as pH, ionic strength and coexisting ions. As a result, nZVI is typically present as a core-shell structure, i.e., the ZVI core wrapped in the iron (hydr)oxide (magnetite) shell (Nurmi et al, 2005;Yan et al, 2010b).…”
Section: Factors Affecting Properties and Effectiveness Of Stabilizedmentioning
confidence: 99%
“…Investigations for the remediation of radionuclides, however, remains less widely researched and includes: barium, [27], pertechnetate [21], [22] and uranium. [20], [28], [29], [30], [31], [32], [33], [34], [35] As demonstrated by [30], uranium uptake onto nZVI typically occurs via sorption and then surfacemediated chemical reduction. In comparison to the body of work reported for uranium, the uptake of plutonium by nZVI has not, as far as we are aware, been previously reported.…”
Section: Introductionmentioning
confidence: 99%